Novel Approaches for the Treatment of Familial Hypercholesterolemia - Bonanni, L.; Cutolo, A.; Dalla Vestra, M. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Familial hypercholesterolemia (FH) is an autosomal disorder characterized by increased levels of total cholesterol and low density lipoprotein (LDL) cholesterol.The extent of underdiagnosis and undertreatment of individuals with FH is largely unknown.The LDL-lowering capacity of statins in combination with other lipid-lowering drugs is maximally around 50–60%. FH patients have a strongly elevated LDL-C and in most cases maximal current treatment is not sufficient to reach the desired LDL targets.Therefore, FH patients have a large residual cardiovascular risk despite the use of statins and there is a medical need for new additional drugs to further lower LDL-C in patients with FH to improve their prognosis.PCSK9 inhibitors have shown great efficacy in lowering lipids with very few side effects. No synergism between statins and PCSK9 inhibition was observed in many trials, allowing clinicians to select a statin dose before considering the initiation of PCSK9-inhibitor therapy.In patients with FH, who are at risk for markedly accelerated atherosclerosis and premature cardiovascular death, also treatment with lomitapide or mipomersen has the potential to reduce the risk of atherosclerotic cardiovascular disease and premature mortality.These new drugs will be probably reserved for the most severely affected FH patients and could help clinicians to reduce their residual cardiovascular risk.
Keywords: familial hypercholesterolemia; PSCK9 inhibitors; evolocumab; alirocumab; mipomersen; lomitapide